(untitled) (Journal of Pure & Applied Sciences, 2022)
Due to the change of some drugs and natural products in the chemical components or chemical structure by exposing them to a laser beam or light, and the effect of heavy metals that may be present in them as a component in them, or as impurities in some medicines, colored dyes, and natural products. The presence of light and laser beam has been studied at time 40 minutes. There are chemical reactions or chemical bonds that may form between the metal ions of medicines such as ibuprofen, folic acid, librex, ranitidine, albendazole and the iron drug, except for Ca 2+ and Ni 2+ because they have the same λ max, and, the pigments found in carrots, red cabbage, beets, turmeric, and maringa , sage, excluding Ca 2+ and Ni 2+ due to having the same λ max, beet, folic acid, iporphine, and, turmeric had the most changes with metal ions, Cu, Ca, Ag, Ni, Fe, Cr, Cd, Pb, Zn and Mn ions after inducing the laser beam. The Ca 2+, and Ni 2+ ions are the most stable ions with all drugs, and pigments extracted from natural products than the rest of the other ions. Previous studies focused on studying the effect of the laser beam on chemical compounds, both separately. In this study, they focused on the effect of the laser beam on medicines and natural dyes, as well as what they may contain of heavy metals or impurities and the chemical changes that occur with them.